2020
DOI: 10.1021/acsmacrolett.0c00609
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Asymmetric Membrane Formation in Nonsolvent-Induced Phase Separation

Abstract: We report the first simulations of nonsolvent-induced phase separation (NIPS) that predict membrane microstructures with graded asymmetric pore size distribution. In NIPS, a polymer solution film is immersed in a nonsolvent bath, enriching the film in nonsolvent, and leading to phase separation that forms a solid polymer-rich membrane matrix and polymer-poor membrane pores. We demonstrate how mass-transfer-induced spinodal decomposition, thermal fluctuations, and glass-transition dynamicsimplemented with mobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 29 publications
1
66
0
Order By: Relevance
“…NIPS has been intensively explored in the fabrication of membrane structures by immersing a preformed structure in a water bath or in the formation of porous fiber structures by deliberately incorporating a considerable amount of water in the polymer solution. [ 51–55 ] A key feature of our method is the ambient humidity‐based fabrication of porous P(VDF‐TrFE) fibers. According to the Flory–Huggins solution theory, [ 56,57 ] the Gibbs free energy of mixing, Δ G m for a polymer–solvent–nonsolvent ternary system under constant temperature ( T ) and pressure ( P ) can be calculated as follows ΔGnormalm= ΔHnormalmTΔSnormalm ΔGnormalm= RTN1lnφ1+N2lnφ2+N3lnφ3+N1φ2g12u2 +N1φ3χ13+N2φ3χ23 χ13= ln1φ3+φ3φ32 g12u2= α+β1γu2 χ23= Vδ2δ32/RT<...>…”
Section: Resultsmentioning
confidence: 99%
“…NIPS has been intensively explored in the fabrication of membrane structures by immersing a preformed structure in a water bath or in the formation of porous fiber structures by deliberately incorporating a considerable amount of water in the polymer solution. [ 51–55 ] A key feature of our method is the ambient humidity‐based fabrication of porous P(VDF‐TrFE) fibers. According to the Flory–Huggins solution theory, [ 56,57 ] the Gibbs free energy of mixing, Δ G m for a polymer–solvent–nonsolvent ternary system under constant temperature ( T ) and pressure ( P ) can be calculated as follows ΔGnormalm= ΔHnormalmTΔSnormalm ΔGnormalm= RTN1lnφ1+N2lnφ2+N3lnφ3+N1φ2g12u2 +N1φ3χ13+N2φ3χ23 χ13= ln1φ3+φ3φ32 g12u2= α+β1γu2 χ23= Vδ2δ32/RT<...>…”
Section: Resultsmentioning
confidence: 99%
“…A similar flow trend can be observed at t = 250 in cases (I) and (II) (results are not shown here due to space restriction). Although the solvent's free movement does not change any basic features of the phase separation, it becomes particularly important for the NIPS process where the solvent needs to move across the interface between the polymer solution and the water 7,9,[20][21][22] .…”
Section: Resultsmentioning
confidence: 99%
“…In reality, these parameters vary with the concentration and affect the phase separation to some degree. Indeed, some previous studies showed in simulations that the concentration dependency of L αβ and η could be crucial for the formation of the glassy polymerrich domains 28 and asymmetric polymeric membranes formed in the NIPS process 9,21,22 . It should be emphasized here that both viscous and elastic features of the polymer solution are fundamentally essential for the viscoelastic phase separation; a simple addition of the concentration-dependent parameters into the diffusion or viscous model may not be sufficient to reproduce the frozen and recovering features of the viscoelastic phase separation simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…(22) 35,39 . Other approaches to capture dynamics related to glass-transition in systems, particularly with a polymer and solvent, have also been explored in the literature 40,41 . The interested reader is advised to look through the various citations included in this section for additional detail.…”
Section: Mobility Coefficientmentioning
confidence: 99%